The Impact of Implementing the Independent Curriculum Based on Project-Based Learning on Arabic Reading Skills (Maharoh Qirāah) at State Islamic Junior High School - Hairuddin Arsyad; Asep Sopian; Maman Abdurrahman; Bening Anjaswara (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to analyze the impact of implementing the Independent Curriculum based on Project-Based Learning (PjBL) on Arabic reading skills (Maharoh Qirāah) in learning at Madrasah Tsanawiyah Negeri 1 Bandung. This study employs a qualitative approach, collecting data through observations, interviews with Arabic language teachers, student questionnaires, and documentation of learning activities. The results indicate that the implementation of the Independent Curriculum based on PjBL has a positive impact on Maharoh Qirāah learning. The project-based approach has been proven to enhance students' interest and motivation, placing them in the